Pengaruh Kualitas Pelayanan Dan Strategi Promosi Terhadap Kepuasan Pelanggan Pada Pondok Nyoman Bagus Di Pererenan Mengwi - pratiwi, Ni Putu Dian Putri; Sugianingrat, IAP Widani; Suartina, I Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study is to determine the effect of both partial and simultaneous quality of service and promotional strategies on customer satisfaction. This study was conducted at Pondok Nyoman Bagus Di Pererenan Mengwi, with a population of 1,440 people and a sample of 94 people using the technique of slovin and with the method of determining samples using non random sampling. The research instruments used in this study are validity tests and reliability tests, then classical assumption tests and multiple linear regression analysis. Based on the results of the study, it was found that partially the quality of service and promotional strategies had a positive and significant effect on customer satisfaction at Pondok Nyoman Bagus in Pererenan Mengwi. The quality of service and promotional strategies simultaneously have a positive and significant effect on customer satisfaction at Pondok Nyoman Bagus in Pererenan Mengwi. Advice given to maintain a friendly quality of service, then optimize promotional strategies through social media to increase customer visits.